Deep coal geomechanical influence mechanism and its control factors of Daji Block in Ordos Basin - Xia YAN; Xianyue XIONG; Fengyin XU; Yueyu YU; Shuguang LI; Feng WANG; Jingshou LIU; Yanqing FENG; Zhitan TANG; Zhenji WEI (Meitan xuebao)
Influence mechanism of rock mechanical properties and microstructure, the lithological combination of roof/floor, and coal thickness and gangue thickness on their stress of deep coal seam are unclear, which restricts differentiated gas reservoir engineering design, optimization of parameters for large-scale fracturing transformation design, and significant increase in single well production. The single well distribution characteristics of static rock mechanics parameters were determined using triaxial compression tests, Brazilian splitting tests, triaxial shear tests, and array acoustic logging curves.The current stress levels of coal seams, roof and floor in the study area were determined through differential strain experiments. A three-dimensional geomechanical model was constructed based on the results of mechanical experiments, and stress simulations were carried out under different microstructural shapes, lithological combinations, coal rock thickness, and gangue thickness conditions. The results show that： ① The average values for the Young's modulus, Poisson's ratio,tensile strength of deep coal are 7.19 GPa, 0.32, and 2.68 GPa respectively, and the average values for the vertical, primary minimum and maximum stresses are 51.78, 43.66, and 37.57 MPa respectively. ② Numerical simulation shows that coal microstructure, seam thickness and roof and floor lithology combination have great influence on coal rock in-situ stress. Under the same roof and floor conditions, the minimum horizontal principal stress of coal seam increases gradually during the transition from positive microstructure to negative microstructure, the minimum horizontal principal stress of the coal seam gradually increases and the stress in the negative structural area is greater than that in the positive and gentle structural areas. As the difference in mechanical properties between the coal seam and the surrounding rock increases, the stress in the coal seam shows a decreasing trend, with the magnitude of the decrease being negative structural > positive structural > gentle area. ③ Six combinations of roof/floor rock types of deep 8th coal seam in the Ordos Basin were classified, among which the minimum horizontal principal stress of coal rock under the combination of roof limestone and floor sandstone was the smallest, and under the combination of roof mudstone and floor mudstone was the largest. The greater the difference in mechanical properties between the roof and floor and the coal seam, the smaller the coal rock stress value. ④ When other conditions are the same, as the thickness of the coal seam increases, the horizontal principal stress and horizontal principal stress difference of the coal rock generally show an increasing trend. The influence of thickness changes on the stress of thin coal seams is more sensitive when the coal seam thickness is less than 4 m. After the thickness of the coal seam is greater than 4-6 m, the increase in horizontal principal stress and horizontal principal stress difference slows down. When the thickness of the coal seam increases from 2 m to 10 m, the minimum and maximum horizontal principal stress increases by 12.9% and 23.3% respectively, and the increase in horizontal principal stress difference reaches 98.3%.⑤ As the thickness of the gangue increases from 0.5 m to 7 m, the horizontal principal stress and stress difference of the gangue decrease significantly by 34.1%. When the thickness of the gangue is greater than 3 m, the decrease in horizontal principal stress and stress difference of the gangue slows down.The above new achievements and insights provide important experimental and theoretical guidance for the division of deep coalbed methane development plan optimization, engineering differentiation design, and analysis of production differences,etc.